Feasibility of Telemedicine Deployment in Major Public Hospitals: A Case Study in Yazd - Mohammad Ebrahim Eghbali Zarch; Razieh Montazeralfaraj; Farimah Shamsi; Mohsen Pakdaman; GHasem Taheri; Mohammad Aghily; Mohammad Amin Bahrami (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Health care organizations are faced with a new technology called telemedicine which provides a platform for remote cooperation, training, and consulting. Telemedicine is the use of information technology for clinical care of patients. This study aimed to establish the feasibility of telemedicine in two educational hospitals of Yazd. Methods: This cross - sectional study was conducted in 2014. Census and random sampling were applied to recruit 200 out of 722 clinical and administrative staffs of both hospitals. Data were then collected through a standardized three-part questionnaire entitled "telemedicine measurement tools". The first two parts of the instrument were in the form of checklist that evaluated the infrastructure, administrative culture, and education dimensions. Questionnaires were distributed among hospitals' managers and IT staffs. The third part of the questionnaire was in a five-item Likert questionnaire format that evaluated staff preparation and also any obstacles to the deployment of telemedicine from the employees' perspectives. Data were analyzed through SPSS18 software and by using descriptive statistics, frequency, and percentage. Results: Providing raining and providing care were selected as the best applications in telemedicine by respectively 82.4% and 76.2% of respondents. Additionally, lack of technical staff and insufficient bandwidth in telemedicine were reported by respectively 85.4% and 77.8% of participants as the biggest barriers for use of telemedicine. Distance learning and remote monitoring were experienced by 14.5% and 10% of employees, respectively. There was no strategic plan and support for the use of telemedicine in the two hospitals. Employees had the necessary knowledge on the benefits of telemedicine, as well as barriers to its deployment. Technical infrastructure required for the deployment of telemedicine at the two hospitals was not available. Conclusion: For the deployment of telemedicine, the two hospitals should invest in technical infrastructure and administrative culture. Also, the preparation of the two hospitals' staffs is the reliable implementation of this plan.